Corporate Governance Dynamics in Saudi Arabia: Audit Committee Composition, Family Ownership, and Financial Performance - Sheela, Sundarasen; Alsmady, Ahnaf Ali; Izani, Ibrahim; Krishna, Tanaraj (Migration Letters, 2024)
The purpose of this research is to examine how the audit committee composition, focusing on independence and the presence of external financial experts, impacts a firm’s performance metrics (Tobin’s-Q and Return on Equity-ROE) in the Kingdom of Saudi Arabia (KSA). Additionally, the study aims to understand how family ownership influences this relationship. The research undertook ordinary least squares (OLS) regression analysis on a dataset comprising 485 firm-year observations. The results show a positive association between having independent directors on the audit committee (AudC) and both Tobin’s-Q and ROE. When the audit committee includes external financial experts, it is linked to a higher ROE but a lower Tobin’s-Q. However, the presence of family ownership acts as a negative moderator in these associations, counteracting the positive effects of the audit committee’s composition on firm performance. This indicates that, in certain institutional settings, investors view audit committee independence as detrimental, impacting their assessment of the firm’s value. This study sheds light on the nuanced understanding of how the composition and utilization of audit committees play out in a specific institutional context, especially within public family-owned firms. It emphasizes the need for a careful consideration of audit committee composition, tailored to the unique business environment of the firm. Regulatory requirements aimed at safeguarding non-family investors may not align well with the dynamics of family businesses. This research significantly contributes to the understanding of corporate governance and its application in family-owned enterprises.